Morphology Improvement of Sandblasted and Acid-Etched Titanium Surface and Osteoblast Attachment Promotion by Hydroxyapatite Coating. Issue 1 (January 2015) - Xu, Sun; Xiaoyu, Yang; Yuan, Su; Minhua, Teng; Jian, Liao; Aidi, Niu; Xing, Liang
Abstract The sandblasting-acid-etched (SLA) technique and hydroxyapatite (HA) deposition are the two methods widely used to improve surface characteristics of titanium implants. In the current study, a layer of HA was deposited on SLA-treated titanium (SLA-Ti) by a simple deposition method. The surface topography and surface roughness of SLA-Ti and HA-coated titanium (HA-Ti) were evaluated using scanning electron microscope (SEM) and atomic force microscope (AFM). Protein adsorption, osteoblast chemotaxis as well as osteoblast attachment on both Ti surfaces were additionally analyzed. The results show that SLA-Ti surface is covered with uniform, multiple micropores, whereas HA-Ti surface is covered with a large number of uniform microparticles under multiple microporous background. In comparison to SLA-Ti, the surface roughness of HA-Ti surface is lower. The protein adsorption on SLA-Ti and HA-Ti surfaces is generally even, and the chemotaxis of osteoblast have no differences. After 12 and 24 h of incubation, more osteoblasts are adhered to the HA-Ti surface and more osteoblast-osteoblast connection is observed on HA-Ti surface compared to SLA-Ti surface. These findings demonstrate that HA coating deposited on SLA-Ti surface improves SLA-Ti surface morphology and promotes osteoblast attachment in vitro.